Cytokine and chemokine kinetics in natural human dengue infection as predictors of disease outcome - Natnicha Jiravejchakul; Wilawan Chan-in; Walairat Thuncharoen; DENFREE Thailand; Anavaj Sakuntabhai; Pratap Singhasivanon; Swangjit Suraamornkul; Tawatchai Yingtaweesak; Khajohnpong Manopwisedjaroen; Nada Pitabut; Sasikanya Thaloengsok; Thaneeya Duangchinda; et al. (Scientific Reports, 2025)
Dengue is an important tropical disease with considerable global impact. Despite this, there remains an urgent need for reliable biomarkers to predict disease severity, as well as effective antiviral drugs and targeted treatments. In this study, we conducted a comprehensive profiling of 41 plasma mediators in patients with asymptomatic dengue (AD) and symptomatic dengue (SD), which includes mild dengue fever (DF) and severe dengue hemorrhagic fever (DHF). Our findings revealed that the levels of nearly all measured mediators were consistently lower in AD compared to SD patients, suggesting a potential protective cytokine response signature. Time-course cytokine analysis in SD shown significantly elevated levels of pro-inflammatory cytokines and chemokines associated with inflammation and viral clearance upon the acute phase, while various growth factors were elevated during the convalescence. Notably, we identified elevated IL-15 levels in DHF patients three days before fever subsidence, highlighting its potential as an early prognostic biomarker for severe disease outcomes. Furthermore, prolonged high levels of IL-8 and IP-10 in DHF during the critical period may contribute to dengue immunopathogenesis. This study advances the understanding of cytokine dynamics in the natural course of human dengue infection, providing valuable insights for the development of targeted treatments and prognostic biomarkers.
Keywords: Mosquito-borne diseases and control; Viral Infections and Vectors; Malaria Research and Control